Exogenous Applications of Brassinosteroids Improve Color of Red Table Grape (Vitis vinifera L. Cv. “Redglobe”) Berries - Vergara, Alexis E.; Díaz, Katy; Carvajal, Rodrigo; Espinoza, Luis; Alcalde, José A.; Pérez-Donoso, Alonso G. (Frontiers in Plant Science, 2018)
Color and other quality parameters of ‘Redglobe’ grape (Vitis vinifera L.) berries were evaluated after treatment with brassinosteroid (BR) analogs. Three BRs analogs (24-epibrassinolide, Triol or Lactone) were applied at three concentrations (0.0, 0.4 or 0.8 mg·L-1), at the onset of veraison. A commercial formulation (B-2000®) was also applied in accordance with the recommendations of manufacturer (0.06 mg·L-1). The tested BR analogs were effective at improving the color of the berries (evaluated as the color index for red grapes, CIRG), increasing the levels of soluble solids and anthocyanins, and changing the groups of anthocyanins present without altering other quality and yield parameters. The effects of BR analogs on the color enhancement could be explained by an increase in soluble solids content and/or anthocyanin content. Treatment with 24-epibrassinolide (at 0.4 mg·L-1) or the commercial formulation tended to favor the production of dihydroxylated anthocyanins, which are responsible for the red and pink colors of grape berries. The results indicate that the use of BRs constitutes a potential tool in the production of table grapes. This is the first report of this enhancement effect in a productive context.